Impact of Technology on the Toothbrush - Alonso Leines, Jenny Lizbeth (Mexican Journal of Medical Research ICSA, 2025)
Oral health is a fundamental aspect for the general wellbeing of all people, as it directly affects quality of life and overall health. Maintaining good dental hygiene is key to preventing problems such as cavities, gum disease, bad breath and other oral disorders. However, many people do not brush effectively due to a lack of knowledge about proper technique and the tools necessary for complete oral hygiene. This article aims to explore the different toothbrush options available, focusing especially on how technological advances have enabled the creation of innovative devices that enhance the brushing experience. Through a review of manual toothbrushes, electric toothbrushes and computer-assisted intelligent systems, it seeks to provide a clear view on the most effective tools for maintaining proper dental hygiene. Aimed at anyone interested in improving their oral health, this article aims to teach how to choose the right toothbrush according to individual needs, in addition to presenting technological solutions that facilitate a correct brushing technique. It will also explore modern tools that, through interaction and learning, transform the dental hygiene process into a more effective and motivating experience, promoting a healthy smile over the years.